Catalyst for synthesizing p-dioxanone as well as preparation method and application of catalyst
By preparing a catalyst containing CuO active metal component, the problems of poor catalyst performance and harsh reaction process conditions in the prior art are solved, and the high selectivity and conversion rate of dioxycyclohexanone are achieved, and the process conditions are simplified. And reduce production costs.
Patent Information
- Application Number
- CN202311015817.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, the catalyst performance is poor, the reaction process conditions are harsh, and the active components are used large, resulting in large metal particles size and low dispersion degree, complex surface properties of the catalyst, complex production process, high cost, and long catalyst during use. The cycle life and the selectivity of the product PDO are not ideal.
Provided is a catalyst for the synthesis of pair dioxycyclohexanone, including 80% to 95% support and 5% to 20% CuO active metal component, the catalyst surface hydroxyl density is 0.4 to 1.0 pieces/nm2, and the surface acid amount is 0.01~0.04 mmol/g, the CuO particle size is 0.5~3.0 nm. The catalyst is prepared by heating reflux and hydrolysis reaction of the carrier in an organic solvent containing a copper source. The reflux and hydrolysis reaction of the non-oxygen atmosphere can control the number of hydroxyl groups and the amount of acid on the surface of the catalyst, inhibit side reactions, and improve the selectivity of the target product.
The catalyst has the characteristics of good stability, long life, selectivity and high conversion rate. It can significantly improve the selectivity of dioxycyclohexanone, inhibit the occurrence of side reactions, simplify process conditions, and reduce production costs.
Smart Images

Figure BDA0004391846760000081 
Figure BDA0004391846760000082 
Figure BDA0004391846760000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of p-dioxanone synthesis, and particularly relates to a catalyst for synthesizing p-dioxanone, a preparation method and application thereof. Background Art
[0002] Aliphatic polyester poly(p-dioxanone) (PPDO) has good biocompatibility, bioabsorbability and biodegradability due to the large number of ether bonds and ester bonds in its molecular chain. Its main body and derivatives are widely used in the field of biomedical materials such as surgical sutures, bone plates, and tissue repair. PPDO is mainly obtained by ring-opening polymerization of p-dioxanone (PDO). To prepare PDO polymer PPDO with excellent performance, high-purity monomer PDO must be prepared first. However, so far, due to difficult synthesis conditions and high preparation costs, PDO is not a universal and easily available commercial product, which hinders the further promotion and application of PPDO. In the limited research reports on the synthesis of PDO, the most economical and simple route is to use cheap and easily available diethylene glycol as a raw material and directly synthesize PDO through catalytic dehydrogenation cyclization under the action of a dehydrogenation catalyst. The dehydrogenation catalyst used is mainly composed of alumina, silicon oxide, molecular sieve as a carrier and transition metals such as copper, silver, platinum, and zinc loaded on the carrier. In this route, exploring and finding a dehydrogenation catalyst with high activity, good selectivity and excellent stability is the key to the low-cost synthesis of high-purity PDO.
[0003] CN112473675A discloses a catalyst for preparing p-dioxanone and a method for preparing p-dioxanone. The catalyst contains 46.2% to 46.9% copper oxide, 0.1% to 1% sodium oxide, and the balance is silicon dioxide. The catalyst can be used for the reaction of preparing p-dioxanone. CN 1739852A discloses a catalyst for gas phase dehydrogenation of diethylene glycol to prepare PDO. The catalyst is prepared by coprecipitation method, and the main body is a copper-zinc compound supported by an inert carrier, which has good conversion rate and selectivity, but the active component content is high, between 20% and 90%. CN112724122A discloses a supported dehydrogenation catalyst with hydroxyapatite as a carrier, the active component is a transition metal of group VIIIB or IB, the catalyst has good thermal stability and good recycling performance. However, the catalyst uses an autoclave reactor to dehydrogenate diethylene glycol to produce PDO in the presence of oxygen and solvent. The operating conditions are relatively harsh, and the reaction and separation process are complicated, which is not conducive to large-scale production.
[0004] The existing technology has the problem of poor catalyst performance to varying degrees, and has high requirements for reaction process conditions, large amounts of catalyst active components, and obvious differences in the properties of different carriers, resulting in large metal particle size, low dispersion, and complex catalyst surface properties. In addition, there is no targeted optimization of the catalyst composition and preparation technology, which makes the catalyst production process complicated and costly. In addition, the long cycle life of the catalyst during use and the selectivity of the product PDO are not ideal, which increases the production cost to a certain extent. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a catalyst for synthesizing p-dioxanone, a preparation method thereof and an application thereof. The catalyst is used in the reaction of synthesizing p-dioxanone, can inhibit the occurrence of side reactions, significantly improve the selectivity of the target product, and has good stability, long service life, easy application process conditions and low production cost.
[0006] The first aspect of the present invention provides a catalyst for synthesizing p-dioxanone. The catalyst, based on the mass of the catalyst and the active metal component in terms of oxide, comprises 80% to 95% of a carrier and 5% to 20% of an active metal component; the active metal component is CuO.
[0007] According to the present invention, the hydroxyl density on the catalyst surface is 0.4 to 1.0 per nm. 2 .
[0008] According to the present invention, the surface acid amount of the catalyst is 0.01 to 0.04 mmol / g.
[0009] According to the present invention, the CuO particle size is 0.5-3.0 nm. The smaller CuO particle size is beneficial to improving the activity and selectivity of the catalyst in the reaction.
[0010] According to the present invention, the carrier is selected from at least one of amorphous silica, SBA-15, MCM-41, and all-silicon ZSM-5.
[0011] The second aspect of the present invention provides a method for preparing the above catalyst. The method comprises:
[0012] (1) immersing the support in an organic solvent containing a copper source and heating under reflux;
[0013] (2) separating the material obtained in step (1), and immersing the obtained solid product in water for hydrolysis reaction;
[0014] (3) drying and calcining the product after hydrolysis in step (2) to obtain the catalyst.
[0015] According to the present invention, the carrier in step (1) is preferably pretreated to remove surface adsorbed impurities; the pretreatment method is to place the carrier in a negative pressure environment for heating and degassing. The pretreatment conditions are: pressure 1 to 1000 Pa; temperature 120 to 220° C.; treatment time 1 to 6 hours.
[0016] According to the present invention, the copper source in step (1) is an organic copper source; preferably, the copper source includes at least one of copper isopropoxide, copper ethoxide, copper glycolate and copper acetate, preferably at least one of copper ethoxide, copper isopropoxide and copper glycolate. The organic solvent includes at least one of toluene, xylene, ethylbenzene, cyclohexane and methylcyclohexane; the mass ratio of the copper source to the organic solvent is 1:30 to 80.
[0017] According to the present invention, the temperature of the heating reflux in step (1) is 80 to 150° C. The heating reflux time is 2 to 8 hours. The atmosphere of the heating reflux is a non-oxygen atmosphere. The non-oxygen atmosphere includes at least one of nitrogen, argon, and helium.
[0018] According to the present invention, the separation described in step (2) can be carried out in a conventional manner, such as filtering. The solid product obtained in step (2) can be washed and dried before the hydrolysis reaction. Preferably, it is dried at 40 to 80° C. for 4 to 8 hours. The washing can be carried out using an organic solvent to remove unreacted materials. The organic solvent used for washing the solid includes at least one of n-hexane, cyclohexane, and acetone.
[0019] According to the present invention, the hydrolysis reaction time in step (2) is 1 to 8 hours, and the temperature is 10 to 30° C. The hydrolysis reaction is carried out under stirring. In the reaction system of step (2), the solid-liquid mass ratio is 1:5 to 20. The water is deionized water.
[0020] According to the present invention, the drying conditions in step (3) are: drying temperature 100-150° C., drying time 10-30 hours. The roasting temperature is 200-550° C., roasting time is 2-8 hours. The roasting equipment is a muffle furnace.
[0021] According to the present invention, step (3) may further include a molding step after calcination. The molding may be tableting. The tableting equipment is preferably an electric tableting machine. The tableting pressure is 10 to 20 MPa. After tableting, the catalyst particles of 10 to 20 meshes are obtained by crushing and screening.
[0022] The third aspect of the present invention provides the use of the above catalyst or the catalyst prepared by the above method in the dehydrogenation of diethylene glycol to synthesize p-dioxanone.
[0023] According to the present invention, the catalyst is subjected to reduction treatment before use, wherein the catalyst is placed in a reactor and subjected to reduction treatment in the presence of a reducing gas.
[0024] According to the present invention, the reduction temperature is 150-300°C, and the reduction time is 4-8 hours. The reducing gas includes at least one of hydrogen, ammonia and carbon monoxide. The reactor is a fixed bed reactor.
[0025] According to the present invention, after the reduction treatment, the reactor temperature is adjusted to the reaction temperature, the atmosphere is switched to a reaction atmosphere, and the raw material is gasified and then contacted with the catalyst for reaction. The reaction atmosphere is a mixed gas of hydrogen and nitrogen, preferably, the ratio of hydrogen to nitrogen is 0.1 to 5:1 by volume.
[0026] According to the present invention, the dehydrogenation reaction temperature is 250-300°C; the reaction pressure is 0.05-0.5 MPa; the molar ratio of diethylene glycol to hydrogen is 1:0.2-5; the volume space velocity LHSV of the feed liquid of diethylene glycol is 0.1-5h -1 .
[0027] Compared with the prior art, the present invention has the following main beneficial effects:
[0028] (1) The catalyst of the present invention comprises 80% to 95% of a carrier and 5% to 20% of CuO; wherein the catalyst surface hydroxyl density is 0.4 to 1.0 per nm 2 , and the surface acid amount of the catalyst is 0.01 to 0.04 mmol / g. The catalyst has low active metal content, high dispersion, and has uniform single-point dispersed active components. The catalyst is applied to the synthesis of p-dioxanone and has the characteristics of good stability, long life, high selectivity and conversion rate. In addition, the catalyst surface has low hydroxyl density and low catalyst surface acid amount, which is conducive to inhibiting the occurrence of the side reaction of diethylene glycol dehydration to form dioxane, thereby improving the selectivity of the target product.
[0029] (2) The preparation method of the catalyst of the present invention includes the steps of heating the carrier under reflux in an organic solvent containing a copper source and then hydrolyzing it. The heating under reflux and hydrolysis reaction in a non-oxygen atmosphere can control the number of hydroxyl groups on the catalyst surface through reaction consumption, and reduce the amount of acid on the catalyst surface. The catalyst prepared by this method can inhibit the occurrence of side reactions and improve the selectivity of the target product to dioxanone. At the same time, the process conditions are easy to achieve during the application process, the equipment operation steps are simple, and the energy and material consumption are small, so that the production cost of dioxanone PDO is greatly reduced.
[0030] (3) In the application of the present invention, the process conditions of the catalyst application method are easy to achieve, the equipment operation steps are simple, and the energy and material consumption are small, so that the production cost of dioxanone PDO is greatly reduced. The catalyst can be used in the reaction to significantly improve the selectivity of the target product and the raw material conversion rate. DETAILED DESCRIPTION
[0031] In order to better understand the present invention, the technical solution of the present invention is further described in detail below through some embodiments, but these embodiments should not be considered as limiting the present invention.
[0032] In the present invention, after the reaction product is condensed and separated, the product components are analyzed by gas chromatography to calculate the conversion rate of diethylene glycol and the selectivity of the target product PDO.
[0033] In the present invention, the amount of acid on the catalyst surface is determined by the NH3-TPD method. 10 vol% NH3 / Ar is performed on a BELCATⅡ, MicrotracBEL instrument. Before the sample is tested, it is first purged in Ar at 200°C for 2 hours, and after cooling to 100°C, the sample adsorbs 10 vol% NH3 / Ar for 30 minutes, and then switches to Ar purging for 1 hour. The TPD curve is collected from 100°C to 600°C, with a heating rate of 5°C / min.
[0034] In the present invention, the hydroxyl density on the catalyst surface is measured by a JASCO 4100 FT-IR infrared spectrometer with a collection range of 400 to 4000 cm -1 , scan times 64, resolution 4cm -1 .
[0035] In the present invention, the CuO particle size is calculated based on the Scherrer formula according to the XRD data. The XRD data is tested by Philip X'pert Pro diffractometer. The X-ray radiation source is Cu target Kα ray (λ=0.15408nm) filtered by Ni filter, the collection step is 0.06° / s, the X-ray tube operating voltage is 40kV, and the current is 40mA.
[0036] In the present invention, the room temperature described in each example is 20°C.
[0037] In the present invention, the diethylene glycol conversion % and the dioxanone selectivity % are molar percentages.
[0038] In the present invention, the catalyst stability data of each example is shown in Table 2.
[0039] Example 1
[0040] Weigh 10.0g of amorphous silica carrier and place it in a round-bottom flask. Connect the flask to an oil pump vacuum system, set the system pressure to 800Pa, and use a heating jacket to heat the flask to 200℃. Degas the carrier for 2h to remove surface adsorbed impurities. After stopping heating and cooling to room temperature, seal the flask and transfer it to a glove box, and add 100g of anhydrous toluene solution containing 3.024g of copper isopropoxide to the treated carrier. The mixed solution is taken out of the glove box, the container is filled with Ar gas atmosphere, and heated to 120℃ and refluxed for 3h to allow the copper salt to fully react with the carrier surface. After cooling to room temperature, filter the mixed solution, and wash the obtained solid with n-hexane to remove the unreacted precursor. The solid is then dried in an oven at 40℃ for 4h. At room temperature, the dried solid is dispersed in deionized water at a solid-liquid ratio of 1:10 and stirred for 2h to hydrolyze the precursor. Finally, the dispersion was filtered, and the obtained solid was dried in an oven at 100°C for 12 hours, and then transferred to a muffle furnace and calcined at 300°C for 4 hours to obtain catalyst powder. The powder sample was crushed and sieved using an electric tablet press to obtain catalyst particles with a particle size of 10 to 20 mesh, which was recorded as Cu@Si-1. The properties of the catalyst are shown in Table 1.
[0041] Take 10ml of catalyst and load it into a fixed bed reactor. Pass 100ml / min of hydrogen and heat to 200℃ for 4h of reduction treatment. After the reduction is completed, the atmosphere is switched to a nitrogen-hydrogen mixture with a volume ratio of nitrogen to hydrogen of 5:1. The system pressure is adjusted to 0.1MPa and the temperature is 260℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw materials are passed into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 1h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0042] Example 2
[0043] Weigh 10.0g of SBA-15 carrier and place it in a round-bottom flask. Connect the flask to the oil pump vacuum system, set the system pressure to 100Pa, and use a heating jacket to heat the flask to 150℃. Degas the carrier for 4h to remove surface adsorbed impurities. After stopping heating and cooling to room temperature, seal the flask and transfer it to the glove box, and add 100g of anhydrous toluene solution dissolved with 2.557g of ethanol copper to the treated carrier. The mixed solution is taken out of the glove box, the container is filled with N2 gas atmosphere, and heated to 140℃ and refluxed for 4h to allow the copper salt to fully react with the carrier surface. After cooling to room temperature, filter the mixed solution, and wash the obtained solid with n-hexane to remove the unreacted precursor. The solid is then dried in a 40℃ oven for 4h. At room temperature, the dried solid is dispersed in deionized water at a solid-liquid ratio of 1:10 and stirred for 2h to hydrolyze the precursor. Finally, the dispersion was filtered, and the obtained solid was dried in an oven at 100°C for 12 hours, and then transferred to a muffle furnace and calcined at 350°C for 4 hours to obtain catalyst powder. The powder sample was crushed and sieved using an electric tablet press to obtain catalyst particles with a particle size of 10 to 20 mesh, which were recorded as Cu@Si-2. The properties of the catalyst are shown in Table 1.
[0044] Take 10ml of catalyst and load it into the fixed bed reactor, introduce 50ml / min of hydrogen and heat to 160℃ for 4h of reduction treatment. After the reduction is completed, the atmosphere is switched to a nitrogen-hydrogen mixture with a volume ratio of nitrogen to hydrogen of 10:1. The system pressure is adjusted to 0.1MPa and the temperature is 280℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw material is introduced into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 1h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0045] Example 3
[0046] Weigh 10.0g of MCM-41 carrier and place it in a round-bottom flask. Connect the flask to an oil pump vacuum system, set the system pressure to 500Pa, and use a heating jacket to heat the flask to 180°C. Degas the carrier for 2h to remove surface adsorbed impurities. After stopping heating and cooling to room temperature, seal the flask and transfer it to a glove box, and add 100g of anhydrous toluene solution containing 3.024g of copper isopropoxide to the treated carrier. The mixed solution is taken out of the glove box, the container is filled with a He gas atmosphere, and heated to 140°C and refluxed for 3h to allow the copper salt to fully react with the carrier surface. After cooling to room temperature, filter the mixed solution, and wash the obtained solid with acetone to remove unreacted precursors. The solid is then dried in an oven at 40°C for 4h. At room temperature, the dried solid is dispersed in deionized water at a solid-liquid ratio of 1:10 and stirred for 4h to hydrolyze the precursor. Finally, the dispersion was filtered, and the obtained solid was dried in an oven at 100°C for 12 hours, and then transferred to a muffle furnace for calcination at 350°C for 4 hours to obtain catalyst powder. The powder sample was crushed and sieved using an electric tablet press to obtain catalyst particles with a particle size of 10 to 20 mesh, which were recorded as Cu@Si-3. The properties of the catalyst are shown in Table 1.
[0047] Take 10ml of catalyst and load it into the fixed bed reactor. Then, introduce 100ml / min of hydrogen and heat to 220℃ for 4h of reduction treatment. After the reduction, the atmosphere is switched to a nitrogen-hydrogen mixture with a volume ratio of nitrogen to hydrogen of 3:1. The system pressure is adjusted to 0.1MPa and the temperature is 260℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw material is introduced into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 1h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0048] Example 4
[0049] Weigh 10.0g of all-silicon ZSM-5 carrier and place it in a round-bottom flask. Connect the flask to an oil pump vacuum system, set the system pressure to 600Pa, and use a heating jacket to heat the flask to 220℃. Degas the carrier for 2h to remove surface adsorbed impurities. After stopping heating and cooling to room temperature, seal the flask and transfer it to a glove box, and add 100g of anhydrous toluene solution containing 3.024g of copper isopropoxide to the treated carrier. The mixed solution is taken out of the glove box, the container is filled with Ar gas atmosphere, and heated to 120℃ and refluxed for 3h to allow the copper salt to fully react with the carrier surface. After cooling to room temperature, filter the mixed solution, and wash the obtained solid with cyclohexane to remove the unreacted precursor. The solid is then dried in an oven at 40℃ for 4h. At room temperature, the dried solid is dispersed in 100g of deionized water at a solid-liquid ratio of 1:10 and stirred for 2h to hydrolyze the precursor. Finally, the dispersion was filtered, and the obtained solid was dried in an oven at 100°C for 12 hours, and then transferred to a muffle furnace and calcined at 400°C for 4 hours to obtain catalyst powder. The powder sample was crushed and sieved using an electric tablet press to obtain catalyst particles with a particle size of 10 to 20 mesh, which were recorded as Cu@Si-4. The properties of the catalyst are shown in Table 1.
[0050] Take 10ml of catalyst and load it into the fixed bed reactor. Then, introduce 100ml / min of hydrogen and heat to 200℃ for 4h of reduction treatment. After the reduction is completed, the atmosphere is switched to a nitrogen-hydrogen mixture with a volume ratio of nitrogen to hydrogen of 1:1. The system pressure is adjusted to 0.1MPa and the temperature is 280℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw materials are introduced into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 0.5h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0051] Example 5
[0052] Weigh 10.0g of amorphous silica carrier and place it in a round-bottom flask. Connect the flask to an oil pump vacuum system, set the system pressure to 100Pa, and use a heating jacket to heat the flask to 130°C. Degas the carrier for 4h to remove surface adsorbed impurities. After stopping heating and cooling to room temperature, seal the flask and transfer it to a glove box, and add 100g of p-xylene solution dissolved with 2.557g of ethanol copper to the treated carrier. The mixed solution is taken out of the glove box, the container is filled with He gas atmosphere, and heated to 140°C and refluxed for 4h to allow the copper salt to fully react with the carrier surface. After cooling to room temperature, filter the mixed solution, and wash the obtained solid with hexane to remove the unreacted precursor. The solid is then dried in an oven at 40°C for 4h. At room temperature, the dried solid is dispersed in 100g of deionized water at a solid-liquid ratio of 1:10 and stirred for 2h to hydrolyze the precursor. Finally, the dispersion was filtered, and the obtained solid was dried in an oven at 100°C for 12 hours, and then transferred to a muffle furnace and calcined at 400°C for 4 hours to obtain catalyst powder. The powder sample was crushed and sieved using an electric tablet press to obtain catalyst particles with a particle size of 10 to 20 mesh, which were recorded as Cu@Si-5. The properties of the catalyst are shown in Table 1.
[0053] Take 10ml of catalyst and load it into the fixed bed reactor. Pass 200ml / min of hydrogen and heat to 230℃ for 6h of reduction treatment. After the reduction is completed, the atmosphere is switched to a nitrogen-hydrogen mixture with a volume ratio of nitrogen to hydrogen of 10:1. The system pressure is adjusted to 0.1MPa and the temperature is 300℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw material is passed into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 0.5h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0054] Example 6
[0055] Same as Example 2, except that the copper salt is copper acetate. The amount of copper acetate added is the same as the amount of copper ethoxide added in Example 2, calculated as copper oxide. The test results are shown in Table 1.
[0056] Comparative Example 1
[0057] Weigh 10.0g of amorphous silica carrier and place it in a round-bottom flask. Connect the flask to an oil pump vacuum system, set the system pressure to 800Pa, and use a heating jacket to heat the flask to 200℃. Degas the carrier for 2h to remove surface adsorbed impurities. After stopping heating and cooling to room temperature, seal the flask and transfer it to a glove box, and add 100g of anhydrous toluene solution containing 3.024g of copper isopropoxide to the treated carrier. The mixed solution is taken out of the glove box, the container is filled with Ar gas atmosphere, and heated to 120℃ and refluxed for 3h to allow the copper salt to fully react with the carrier surface. After cooling to room temperature, filter the mixed solution, and wash the obtained solid with n-hexane to remove unreacted precursors. The solid is then dried in an oven at 40℃ for 4h, and then the sample is directly transferred to a muffle furnace without hydrolysis and calcined at 300℃ for 4h to obtain a catalyst powder. The powder sample was pressed by an electric tabletting machine, and the sample tablets were crushed and sieved to obtain catalyst particles with a particle size of 10 to 20 mesh, which was recorded as DB-1. The properties of the catalyst are shown in Table 1.
[0058] Take 10ml of catalyst and load it into a fixed bed reactor. Pass 100ml / min of hydrogen and heat to 200℃ for 4h of reduction treatment. After the reduction is completed, the atmosphere is switched to a mixture of nitrogen and hydrogen. The volume ratio of nitrogen to hydrogen is 5:1. The system pressure is adjusted to 0.1MPa and the temperature is 260℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw material is passed into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 1h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0059] Comparative Example 2
[0060] The amorphous silicon oxide carrier is pretreated to obtain an amorphous silicon oxide carrier after heating and degassing. The pretreatment method of the carrier is the same as that of Example 1.
[0061] Weigh 3.024g of copper isopropoxide in a beaker, add 30g of deionized water and stir to dissolve, then add 10.0g of pretreated amorphous silica carrier to the precursor salt solution, and continue to stir vigorously at room temperature for 2h. Then transfer the mixed solution to an 80℃ oil bath and keep stirring to evaporate the water. After grinding the obtained solid, dry it in an oven at 100℃ for 12h, and then transfer it to a muffle furnace and calcine it at 300℃ for 4h to obtain a catalyst powder. The powder sample is crushed and sieved by an electric tablet press to obtain catalyst particles with a particle size of 10 to 20 mesh, which are recorded as DB-2. The properties of the catalyst are shown in Table 1.
[0062] Take 10ml of catalyst and load it into the fixed bed reactor. Then, introduce 100ml / min of hydrogen and heat to 200℃ for 4h of reduction treatment. After the reduction is completed, the atmosphere is switched to nitrogen and hydrogen mixed gas. The volume ratio of nitrogen to hydrogen is 5:1. The system pressure is adjusted to 0.1MPa and the temperature is 260℃. According to the ratio of diethylene glycol to hydrogen of 1:1, the raw material is introduced into the reactor for dehydrogenation reaction. The volume space velocity of diethylene glycol liquid is 1h -1 The reaction product was condensed to obtain a liquid product. The catalyst test results are shown in Table 1.
[0063] Comparative Example 3
[0064] Same as Example 1, except that the copper salt is copper nitrate. The amount of copper added is the same as that of Example 1, calculated as copper oxide. The test results are shown in Table 1.
[0065] Table 1 Catalyst dehydrogenation reaction effect of each case after 50 hours of reaction
[0066]
[0067] Table 2 Catalyst stability data for each example
[0068]
[0069]
[0070] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for synthesizing p-dioxanone, based on the mass of the catalyst and the active metal components in terms of oxides, comprising: 80% to 95% of a carrier and 5% to 20% of an active metal component; the active metal component is CuO; The catalyst surface hydroxyl density is 0.4 to 1.0 per nm 2 ; The surface acid amount of the catalyst is 0.01 to 0.04 mmol / g.
2. The catalyst according to claim 1, characterized in that The CuO particle size is 0.5-3.0 nm.
3. The catalyst according to claim 1, characterized in that The carrier is selected from at least one of amorphous silica, SBA-15, MCM-41, and all-silicon ZSM-5.
4. A method for preparing a catalyst for synthesizing p-dioxanone according to any one of claims 1 to 3, comprising: (1) immersing the support in an organic solvent containing a copper source and heating under reflux; (2) separating the material obtained in step (1), and immersing the obtained solid product in water for hydrolysis reaction; (3) drying and calcining the product after hydrolysis in step (2) to obtain the catalyst; The atmosphere for heating and refluxing in step (1) is a non-oxygen atmosphere; and the copper source is an organic copper source.
5. The preparation method according to claim 4, characterized in that: The heating reflux temperature in step (1) is 80-150° C.; and / or, the heating reflux time is 2-8 hours; and / or, the non-oxygen atmosphere includes at least one of nitrogen, argon and helium.
6. The preparation method according to claim 4, characterized in that: The copper source in step (1) comprises at least one of copper isopropoxide, copper ethoxide, copper ethylene glycol and copper acetate, preferably at least one of copper ethoxide, copper isopropoxide and copper ethylene glycol.
7. The preparation method according to claim 4, characterized in that: The hydrolysis reaction time in step (2) is 1 to 8 hours, and / or the hydrolysis reaction temperature is 10 to 30°C.
8. The preparation method according to claim 4, characterized in that: In the reaction system of step (2), the solid-liquid mass ratio is 1:5-20.
9. The preparation method according to claim 4, characterized in that: The calcination temperature in step (3) is 200-550° C., and / or the calcination time is 2-8 hours.
10. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 9 in the synthesis of p-dioxanone by dehydrogenation of diethylene glycol.
Citation Information
Patent Citations
Method for preparing p-dioxanone from diethylene glycol and catalyst thereof
CN112724122A
Catalyst for preparing p-cyclodexanone dioxide
CN1739852A
Alkane dehydrogenation catalyst and preparation method thereof
CN104588011A
Method for preparing organic oxygenated compounds by hydrocarbon catalytic selective oxidation
CN105712837A
Double-component composite aluminum oxide high-thermal stability ordered mesopore material and preparation method thereof
CN107115864A